I.YUSUPOV HÁM M.SEYTNIYAZOVLARDÍŃ POEMALARÍNDA ANADIPLOSISLERDIŃ KÓRKEMLIK XÍZMETI - Sayımbetov, Sh.U. (SCIENCE and SOCIETY, 2025)
The article examines the method of repetition of anadiplosis. Theoretical provisions of anadiplosis are presented, the features of its application and artistic tasks in the poems of I.Yusupov and M.Seitniyazov are revealed.